Empirical pricing kernels and investor preferences - Kai Detlefsen; Wolfgang Karl Härdle; Rouslan A. Moro (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper analyzes empirical market utility functions and pricing kernels derived from the DAX and DAX option data for three market regimes. A consistent parametric framework of stochastic volatility is used. All empirical market utility functions show a region of risk proclivity that is reproduced by adopting the hypothesis of heterogeneous individual investors whose utility functions have a switching point between bullish and bearish attitudes. The inverse problem of finding the distribution of individual switching points is formulated in the space of stock returns by discretization as a quadratic optimization problem. The resulting distributions vary over time and correspond to different market regimes.
Keywords: G12; G13; C50; 330; Utility function; pricing kernel; behvioral finance; risl aversion; risk proclivity; Heston model; Anlageverhalten; Risikoaversion; Präferenztheorie; Börsenkurs; Stochastischer Prozess; Volatilität; Schätzung; Deutschland